Is Capital Mobility Good for Public Good Provision? - Gregor Schwerhoff; Ottmar Edenhofer (Center for Economic Studies and ifo Institute (CESifo), 2013)
We set up a general model on capital mobility which contains many of the models in the literature as special cases. The race to the bottom results not from a capital flight effect, but rather from a kind of Laffer curve effect in public good provision. Selectively introducing simplifying assumptions allows reproducing other models and understanding how they bias results in favor or against capital mobility. We then show how the net effect of capital mobility can be positive or negative within the same model depending on the relative capital endowment.
Keywords: D62; H21; H50; H73; H87; 330; capital mobility; interjurisdictional competition; public good provision